Physico-mechanical properties of thermoplastic composite reinforced with kelempayan, oil palm trunk and bamboo as fillers / Siti Zalifah Mahmud ... [et al.] - Mahmud, Siti Zalifah; Mohammad, Noorshashillawati Azura; Suid, Nurul Hamiza; Mohd Zailani, Nur Farhana; Za'abah, Nor Faeza; Mohamed, Siti Habshah; Ahmad Bakri, Noor Fanida; Nik Hussin, Nik Suaidasalma (Universiti Teknologi MARA (UiTM), 2022)
Thermoplastic composite panel can be used for a variety of applications. The wide distribution, renewability and recyclability of lignocelluloses can expand the market for low-cost thermoplastic composites. Lignocellulosic materials from fast growing and plantation species such as lesser-known timber, bamboo and palm tree are promising materials for particulate filler for the production of thermoplastic composite panel due to its accessibility, great substrate behaviour and high yield resources. This study was to determine the physico-mechanical properties of thermoplastic composite panel reinforced with particulate fillers from kelempayan (Neolamarckia cadamba), oil palm (Elaeis guineensis) and betong bamboo (Dendrocalamus asper). This study focused on the effect of particle size and three percent additive to dimensional stability and strength properties of a panel. The polypropylene plastic has been blended with the particulate fillers in a dispersion mixture at the temperature of 180 °C. Then, it was hot pressed for five to nine minutes and the mold was cold pressed for three minutes before the panel was conditioned for testing performance. Preliminary results indicated that smaller particles size with a filler loading ratio of 10 % was easier to disperse in melted polypropylene to produce composite plastic panels as compared to larger particles size which resulted in minimum dimensional changes and higher tensile strength. Statistical analysis has proven that different particle sizes and the supplementary of three percent additive significantly influenced the physico-mechanical properties of the thermoplastic composite panel